State of Charge and State of Health Estimation Using Pseudo Random Binary Sequences and Machine Learning - Muhammad Afnan Aziz Khan (00000319006); Dr Hassan Abdullah Khalid (USPCAS-E, NUST, Islamabad, 2021)
TH-305
Keywords: MS-EEP Thesis; MS Thesis